A teacher’s perspective on values and dilemmas in textbook - SavitriYola; KurniawanEri (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Teaching and learning English in the context of English as a foreign language requires materials that can support the process of learning English. Regarding the content of the materials, it is believed that one of the most vital aspects of a textbook is to engage learners with the content they are dealing with. Previous studies reveal that there are several issues with the use of textbooks. Gender, ideology and culture representation, critical thinking, and pluralism are several issues that arise regarding the content of textbooks. Thus, this study examined the values and dilemmas in the textbook from the teacher’s perspective including how the teacher encountered the issues found in textbooks and in the process of learning and teaching. A narrative inquiry was applied to collect stories and experiences from an EFL teacher of a Madrasah Tsanawiyah through semi-structured interviews. The findings showed that the mentioned issues were found in Can Do English textbook that the teacher used so the teacher made some adjustments to the materials when the content did not fit with values that underpinned the school. Moreover, a few issues were still acceptable to the participant’s view as a teacher and not considered as serious problems. Furthermore, providing students with a textbook that could attract students to engage with its content was the main consideration the teacher made in selecting the textbook for the students.